PERBANDINGAN HASIL BELAJAR MATEMATIKA MODEL PEMBELAJARAN KOOPERATIF TIPE COOP-COOP DENGAN KONVENSIONAL - Zulyadaini Zulyadaini (Universitas Batanghari Jambi, 2016)
Observations of researchers, there are still many the application of conventional learning that is learning centered on teachers, students only listen to, noted and sent do this exercise so learning fun did not happen. This research is research the experiment the sampelnya a random sampling. The final result of this research obtained by means compare study results class the experiment apply model cooperative type coop-coop with the class implementing learning model conventionally often applied in schools in general. The results of the end of the study concluded that mathematics students who apply model cooperative type coop-coop better than conventional learning model.According to the research conducted on the final test (post-test ), the results rata-rata class the experiment 72,2 and results value rata-rata class 65,9 control, as well as from test t Count hipotesis obtained by 2,13 and t tabel of 1,68. From the results of it is evident that thitung larger than ttabel so H0 turned down and H1 accepted. It can be can be concluded that mathematics students who use cooperative learning model type talking stick is better than the mathematics students who use direct learning model.Keywords; Study Results, Learning Model Cooperative Type Coop-Coop, Learning Covensional.